Visitor Perception of Eco-Friendly Resorts Selection in Sri Lanka - Perera ,D.D.I; Atapattu, C (NSBM Green University, 2019)
Tourism is one of the most important industries in the world as well as in Sri Lanka. Therefore, identifying the factors affecting visitor perception on selection of eco-friendly resorts is vital. Visitor perception is highly considered in tourism industry since the success of the industry depends on the participation of tourists who visit Sri Lanka. This study was conducted to identify the perception of visitors on what is their opinion about Eco friendly resorts in Sri Lanka. Main objectives of this study were to find out the factors affecting visitor perception on selection of Eco-friendly resorts and to find out the impact on visitor perception. Independent variables were created based on factors affecting Theory of Planned Behaviour.Identified factors were attitude, subjective norms, perceived behavioral control which were used to determine visitors’ intention to visit an eco-friendly hotel. In this study, the quantitative research design is used. The survey has been conducted to collect data with a quantitative and explanatory approach where a structured survey was used on 150 local tourists who visited eco friendly hotels in Sri Lanka. The respondents were asked to express their agreement or disagreement with a statement on a five point Likert-type scale. Sample was limited to 100 tourists who have visited any of Green hotels in Sri Lanka. The data was analyzed through SPSS software. The findings of the study revealed that the impact of attitude to behavior, subjective norms and perceived behavioral control on guests’ continued intention to use green hotels are significant and positive. The independent variables explained 51.7% of variance approximately in visitor perception by the adjusted R-Squared value. All the hypothesis was accepted except H3 which was tested for the perceived behavioral control factor.
Keywords: Visitor Perception; Eco-Friendly Hotel; Theory of Planned Behavior; Attitude; Subjective norms; perceived behavioral control